Pharmacological inhibition of Src family kinases attenuates hyperuricemic nephropathy - Xiong, Chongxiang; Deng, Jin; Wang, Xin; Hou, Qidi; Zhuang, Shougang (Frontiers in Pharmacology, 2024)
Hyperuricemia is an independent risk factor for chronic kidney disease and contributes to renal fibrosis. This study aims to investigate the effect of Src family kinases (SFK) inhibition on the development of hyperuricemic nephropathy (HN) and the mechanisms involved. In a rat model of HN, feeding rats a mixture of adenine and potassium oxonate increased Src phosphorylation, severe glomerular sclerosis, and renal interstitial fibrosis, accompanied by renal dysfunction and increased urine microalbumin excretion. Administration of PP1, a highly selective SFK inhibitor, prevented renal dysfunction, reduced urine microalbumin, and inhibited activation of renal interstitial fibroblasts and expression of extracellular proteins. PP1 treatment also inhibited hyperuricemia-induced activation of the TGF-β1/Smad3, STAT3 and NF-κB signaling pathways and expression of multiple profibrogenic cytokines/chemokines in the kidney. Furthermore, PP1 treatment significantly reduced serum uric acid levels and xanthine oxidase activity. Thus, blocking Src can attenuate development of HN via a mechanism associated with the suppression of TGF-β1 signaling, inflammation and uric acid production. The results suggest that Src inhibition might be a promising therapeutic strategy for HN.